Pilihan Pengobatan Mikosis Superfisialis dan Profunda di Indonesia - Reqgi First Trasia (LPPM Universitas Sari Mulia, 2022)
Background: Fungal infectious diseases are found cosmopolitan, especially in hot climates. In Indonesia, the frequency of superficial mycoses is still quite high. However, the parasitological review of the current treatment of superficial and deep fungal diseases is still poorly understood. Purpose: This article aims to review the current treatment of superficial and deep mycoses in Indonesia. Methods: Recent literature search, obtained 13 relevant articles for review. Results: In minor superficial mycoses, local (topical) treatment with salicyl, imidazole derivatives, isoconazole, terbinafine cream, cyclopyrox solution and tolnaphthate tincture or ointment may be given. In deep mycoses, itraconazole can be given. Conclusion: Based on the results of the review, it can be concluded that to treat the symptoms caused by superficial mycoses, topical treatment with imidazole derivatives is given, while in deep mycoses, tablets or injections such as amphotericin are given. Keywords: treatment, fungus, mycosis, infection.